2010
DOI: 10.4314/acsj.v15i2.54422
|View full text |Cite
|
Sign up to set email alerts
|

Nematode distribution and damage to yam in central and eastern Uganda

Abstract: Yams (Dioscorea spp.) are food crops of growing significance in sub Saharan Africa. Unfortunately, nematodes are major pests to their production. A study was undertaken in major yam growing areas of Uganda to investigate the association of plant parasitic nematodes with damage symptoms. Nematodes were assessed from tubers, roots and surrounding soil for seven cultivars belonging to Dioscorea alata, D. bulbisiana, D. burkilliana and D. cayenensis at harvest. Pratylenchus sudanensis was found in the greatest den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Research on the staple food crops of an area and awareness of nematode problems in the local farming communities are limited. However, the limited data available in ESA (addressing this weakness is one of the major keys to ameliorating the problem) indicate that PPN are widespread and cause significant losses in bananas, maize, yam, vegetables and fruit crops . The examples and discussions presented here have been selected to demonstrate that nematodes are frequently a limiting factor on a wide range of crops commonly grown in ESA, with particular focus given to Kenya, Tanzania, Uganda and Zimbabwe.…”
Section: Nematode Problems On Key Staple and Economically Important Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the staple food crops of an area and awareness of nematode problems in the local farming communities are limited. However, the limited data available in ESA (addressing this weakness is one of the major keys to ameliorating the problem) indicate that PPN are widespread and cause significant losses in bananas, maize, yam, vegetables and fruit crops . The examples and discussions presented here have been selected to demonstrate that nematodes are frequently a limiting factor on a wide range of crops commonly grown in ESA, with particular focus given to Kenya, Tanzania, Uganda and Zimbabwe.…”
Section: Nematode Problems On Key Staple and Economically Important Cmentioning
confidence: 99%
“…In Uganda, Pratylenchus sudanensis has been observed causing similar symptoms to S. bradys , while RKN are particularly prevalent and damaging, causing rotting and necrosis, especially during storage . Nematode‐damaged tubers used as planting material also reinfect the subsequent crop and so perpetuate the problem . It is possible to achieve control of Scutellonema bradys by hot water treatments of seed tubers, although resistance can be a potentially better way to manage this nematode …”
Section: Nematode Problems On Key Staple and Economically Important Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The cracking symptoms caused by S. bradys were observed on D. alata and on D. rotundata tubers at the harvest. The damages were described in Uganda and in Nigeria as dangerous for roots and tubers as yam in African tropical soil (Mudiope et al, 2007;Amusa et al, 2003). They limit yam yield when they appear in the soil.…”
Section: Climatic Growth Conditionsmentioning
confidence: 99%
“…In addition, International Institute of Tropical Agriculture (IITA, 2011) reported that Nigeria accounted for about 70% of the world production amounting to 17 million tonnes from land area of 2,837,000 hectares. It is a tropical tuber crop grown as a source of carbohydrate but also for use in ceremonial activities (Mudiope et al, 2007). Yam serves as staple food in many tropical and sub-tropical countries of the world and in Nigeria the principal source of carbohydrate.…”
Section: Introductionmentioning
confidence: 99%